(untitled) (Damascus University Journal for the economic and Political sciences, 2022)
This study aimed to determine bank employees’ awareness of the level of applying green human resource management practices and to test the effect of applying these practices on their performance. The study sample consisted of 37 respondents working in human resources management in private Syrian banks listed in the Damascus Stock Exchange. In order to achieve the objectives of the study, the researchers designed a questionnaire to collect data. The results of the research indicated that the respondents’ perception of the concept of green human resource management practices was average. As for their awareness of the level of application of green human resource management practices in Syrian private banks, it was average for all practices except for green rewards, which were at a low level. The results of the multiple logistic regression analysis showed that there is a positive and significant impact of green employment practices, green training and development, green performance evaluation and energy conservation on the performance of employees in banks listed on the Damascus Stock Exchange. While the results indicated that there was no significant effect of green rewards on the performance of employees in these banks. The study recommended the necessity for the human resources departments of private banks to promote green practices in a way that would ensure raising the performance of their employees. The study also recommended the necessity to expand the field of research to include the governmental banking sector and other economic sectors in Syria.